Using a single PR campaign to take over all of Instagram; A perspective on Lie to Eye Advertising Ltd. - Ahmed, Shahariar (Brac University, 2023)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2021.